IPTEKS UPAYA PENINGKATAN HASIL PENERIMAAN PAJAK BERDASARKAN EFEKTIVITAS PELAKSANAAN PEMERIKSAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA MANADO - Karaseran, Grefis; Rundengan, Fanda (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
In the economy in Indonesia alone taxes have a very vital role. Indonesia itself adheres to the self assessment system, this opens a gap for taxpayers to act dishonestly. Therefore the Directorate General of Taxes is obliged to carry out administrative supervision as well as through tax audits. The purpose of the tax audit is to test compliance with the obligations of taxpayers. The research method used was descriptive research based on SP2 and SKP data from Manado Primary Tax Office. Based on three years, namely from 2014, 2015, and 2016 the percentage level of SP2 examination effectiveness is always on a very effective criterion, but in the next two years, from 2017 and 2018, the percentage level of SP2 examination effectiveness has decreased which is in the less effective criteria. Based on SKP data for the past 5 years, the level of acceptance has not been effective because it has reached the set target.Keywords : Effectiveness, Tax Audit, Tax Revenue